The race that segments a nation: Findings from a convenience poll of attitudes toward the Melbourne Cup Thoroughbred horse race, gambling and animal cruelty. - Bethany J Wilson; Kirrilly R Thompson; Paul D McGreevy (PLoS ONE)
The annual Melbourne Cup Thoroughbred horse race has iconic status among many Australians but sits in the context of increasing criticism of the welfare of Thoroughbred racing horses and the ethics of gambling. Despite heated debates and protests playing out in the public domain, there is scant empirical research to document Australian attitudes to the Melbourne Cup, or horse racing more generally. Specifically, little is known about how support for or against the Melbourne Cup correlate with age, gender, income and level of education. To provide a more nuanced understanding of attitudes towards the cup beyond the rudimentary binaries of those who are 'for' or 'against' gambling and horse racing, the purpose of the study was to identify clusters of people with particular views. An opportunistic survey collected data on respondents' gender, age, place of residence, weekly income, employment status and highest level of education, and sought their level of agreement with six statements about the Melbourne Cup, gambling and animal cruelty. Ordinal logistic regression and Chi-square analysis were used to evaluate the age and gender of respondents in clusters respectively. Agreement with the statements revealed some significant associations. Male respondents were at greater odds for agreement with the statement: I regularly bet on horse races (OR = 2.39; 95% CI = 1.78-3.22) as were respondents aged 18-19 years (OR = 2.88; 95% CI = 1.13-7.35) and 20-24 years (OR = 1.90; 95% CI 1.00-3.62) compared with the median 35-40 years age bracket. Agreement with the statement: I will watch the Melbourne Cup but will not place a bet was more likely among the full-time employed (OR = 1.60; 95% CI = 1.10-2.32), for those aged 20-24 years (OR = 1.85; 95% CI = 1.16-2.95). The odds of increasing agreement with the statement: I have never been interested in the Melbourne Cup were multiplied by 0.87 (95% CI = 0.82-0.92) with each successive five-year age bracket. The most useful of the predictor variables for agreement was level of education. The odds of increasing with the statement: I have become less interested in the Melbourne Cup over recent years because of my concerns with gambling were multiplied by 1.09 (95% CI = 1.02-1.15) for each increased level of education. Agreement with the statement: I have become less interested in the Melbourne Cup because of my concerns about animal cruelty was weaker amongst male respondents (OR = 0.62; 95% CI = 0.48-0.80), and those in increasing age brackets (OR = 0.88; 95% CI = 0.83-0.93). A series of six clusters were identified that show how certain attributes of respondents characterise their responses. The authors labelled these clusters "Devotees" (n = 313; 30.4% of respondents), "Flaneurs" (n = 244; 21.8% of respondents), "Disapprovers" (n = 163; 15.9% of respondents), "Casuals" (n = 148; 14.4% of respondents), "Gamblers" (n = 126; 12.3% of respondents) and "Paradoxical-voters" (n = 54; 5.3% of respondents). The implications for support of the Melbourne Cup are explored.